PESONA BATIK BESUREK DALAM KARYA FOTOGRAFI FASHION - PUTRA, JEKA ESA (Institut Seni Indonesia Padangpanjang, 2021)
The development of fashion at this time has a very big influence on one's creativity in creating a design and responding to existing designs. Of the various products that are consumptive goods of this society, one of them is Besurek batik. If in the past batik only touched the functional realm, now in the modern era like now, the function of batik has shifted to become part of fashionBengkulu province besurek batik is usually worn by women aged 30 years and over and is rarely worn by women who are still relatively young. Therefore, the artist makes fashion photography by making batik besurek as the object so that young women or girls are interested in wearing batik besurek clothing with contemporary designs in the form of batik and bright colors Besurek batik is one of the collections of the Bengkulu government with the theme of batik. The process of creating this final project goes through several stages including preparation, elaboration, synthesis, concept realization, work selection and completion. In the creation of this work, the artist carries the traditional concept and directs the work of the photo into a fashion lookbook. The artist also carries out the editing process to perfect this final project. There are 20 photographs that have been selected by the supervisor.